Failure of intravenous pentagastrin challenge to induce panic-like effects in rhesus monkeys. - Rupniak, N; Schaffer, L; Siegl, P; Iversen, S (1993)
We examined the ability of intravenous (i.v.) challenge with pentagastrin to induce behavioural and cardiovascular effects consistent with panic attack in conscious rhesus monkeys. For behavioural evaluation, 4 naive male rhesus monkeys familiar with minimal manual restraint necessary for drug administration received a rapid i.v. bolus of pentagastrin (4, 8 or 16 micrograms/kg) or water on four separate occasions according to a randomised cross-over design. Behaviour was rated by a blind observer continuously during, and for the first 5 min immediately following i.v. injections while the monkey sat on the handler's lap, and then for a further 25 min in an individual observation cage. In separate experiments, the ability of pentagastrin to alter cardiovascular parameters which may accompany panic or anxiety (elevated heart rate and blood pressure) was explored. For cardiovascular studies, 8 male or female rhesus monkeys with femoral artery catheters were chair restrained and received a bolus injection of pentagastrin (4, 8 or 16 micrograms/kg) or saline into the saphenous vein at 30 min intervals. Blood pressure and heart rate were monitored continuously using a Statham Gould pressure transducer. Pentagastrin induced no consistent behavioural or cardiovascular changes. Similar pilot studies using CCK4 also failed to reveal such effects. We conclude that CCK-induced panic-like effects may not be demonstrable following challenge with pentagastrin under laboratory conditions in rhesus monkeys.